(untitled) (REMUNOM, 2025)
Parkinson’s disease (PD) is a neurodegenerative condition that affects the central nervous system, compromising motor control and mainly affects the elderly population. With population aging, diseases such as PD gain greater relevance, requiring more studies of interventions to be applied for rehabilitation aimed at this population. The objective of this study was to identify, through an integrative review, the most effective physiotherapeutic interventions in the literature for the prevention of falls in elderly individuals with PD. The inclusion criteria were articles of controlled and randomized clinical trials from 2007 to 2024, studies that contained samples with a mean age over 60 years and diagnosed with PD; studies involving animals or inaccessible free of charge were excluded. After applying search filters and the process of screening the articles in the PubMED and PEDro databases, 10 studies were included in this review. These studies addressed beneficial and relevant interventions for the prevention of falls in people with PD, through programs based on balance training, strengthening of the lower limbs and postural control training. Although the evaluated interventions showed positive results, more research is needed to improve clinical planning.